On the necessity of new decision-making methods for cancer-associated, symptomatic, pulmonary embolism. Issue 143 (July 2016) - Carmona-Bayonas, A.; Font, C.; Jiménez-Fonseca, P.; Fenoy, Francisco; Otero, R.; Beato, C.; Plasencia, J.; Biosca, M.; Sánchez, M.; Benegas, M.; Calvo-Temprano, D.; Varona, D.; et al.
Abstract: Background: Acute symptomatic pulmonary embolism (PE) varies in its clinical manifestations in patients with cancer and entails specific issues. The objective is to assess the performance of five scores (PESI, sPESI, GPS, POMPE, and RIETE) and a clinical decision rule to predict 30-day mortality. Methods: This is an ambispective, observational, multicenter study that collected episodes of PE in patients with cancer from 13 Spanish centers. The main criterion for comparing scales was the c-indices and 95% confidence intervals (CIs) of the models for predicting 30-day mortality. Results: 585 patients with acute symptomatic PE were recruited. The 30-day mortality rate was 21.3 (95% CI; 18.2–24.8%). The specific scales (POMPE-C and RIETE) were equally effective in discriminating prognosis (c-index of 0.775 and 0.757, respectively). None of these best performing scales was superior to the ECOG-PS with a c-index of 0.724. The remaining scores (PESI, sPESI, and GPS) performed worse, with c-indexes of 0.719, 0.705, and 0.722, respectively. The dichotomic "clinical decision rule" for ambulatory therapy was at least equally reliable in defining a low risk group: in the absence of all exclusion criteria, 30-day mortality was 2%, compared to 5% and 4% in the POMPE-C and RIETE low-risk categories, respectively. Conclusion: The accuracy of the five scales examined was not high enough to rely on to predict 30-day mortality and none of them contribute significantly to qualitative clinical judgment. Highlights: We describe why new decision-making methods are needed for cancer-associated, symptomatic, pulmonary embolism We have evaluated the performance of five prognostic scales and a clinical decision rule (CDR) to predict 30-day mortality None of the five models contributed to qualitative clinical judgment These methods were no better than the ECOG PS or the simple dichotomic classification based on altered vital signs (CDR) A clinically meaningful attempt to further refine the stratification is presented